Чернігівщина років Голодомору (1932-1933) на сторінках часопису "Вісті ВУЦВК": вирощування технічних і кормових культур, тваринництво - Горох, М.В. (Сіверщина в історії України, 2024)
Одним із основних інструментів пропаганди, які активно використовував комуністичний тоталітарний режим, була преса. Центральна преса досліджуваного періоду, яка представлена газетою «Вісті ВУЦВК», є специфічним історичним джерелом, опрацювання якого вимагає детальної верифікації. Часопис містить багатий джерельний потенціал щодо вивчення процесів примусового вилучення продовольчих культур у селян, так званих хлібозаготівель, збору мірчука, насіннєвого матеріалу, конфіскації зерна, що лежало в «куркульських ямах», діяльність «буксирних бригад» тощо, які у 1932–1933 рр. були інструментами чинення геноциду, адже створювали для них життєві умови, несумісні з життям. Чимало уваги редакція приділяла питанням вирощування технічних культур, тваринництву, роботі машинно-тракторних станцій. Винним у всіх негараздах, на переконання радянської преси, був так званий «класово-ворожий» елемент. Газета «Вісті ВУЦВК» рясніла матеріалами про виявлення прихованих «ворогів радянської влади», описом їхніх злочинів, закликами карати винуватців за всією суворістю закону. One of the propaganda tools used by communist totalitarian regime was the press. It helped to implant the mass campaigns and political decisions which were necessary for the regime. «Visti VUTSVK» is a specific historical source which represents the central press of the researched period. It still needs the detailed verification. The magazine has depicted various topics concerning politics, economy, education, cooperation, social and female issues, global problems. Its contributions are the unique source for studying the different aspects of Holodomor (1932–1933). In the middle of the research are the publications dedicated to the cultivation of technical and fodder crops, animal husbandry. The central press is filled with important sources about forceful grain, merchuk, seeds and crops collection and activities of «tug gangs» which during 1932–1933 used to produce fatal living environment for the peasants and in such a way were genocide executives. The editors paid a lot of attention to the issues of growing technical crops, animal husbandry, and the work of machine-tractor stations. Communal and state farms, workmen’s cooperative associations and self-employed farmers had no time to crop the fields, perform pest control, get the crops and deliver it to place of storage or transformation. The plans were too high and there weren’t enough men, knowledge and skills. Moreover there were unwillingness to work, absence of incentive system and senseless tasks. The success ratio was plan performance. According to the soviet press the so-called «class hostile element» was guilty in all troubles and disputes. The pages of «Visti VUTSVK» were filled with materials about exposure of «soviet authority enemies», descriptions of their crimes and appeals to punish them with all the full extent of law.